2014
DOI: 10.1063/1.4900824
|View full text |Cite
|
Sign up to set email alerts
|

Constructing new braided T-categories over monoidal Hom-Hopf algebras

Abstract: Let \documentclass[12pt]{minimal}\begin{document}${\sl Aut}_{mHH}(H)$\end{document}AutmHH(H) denote the set of all automorphisms of a monoidal Hopf algebra H with bijective antipode in the sense of Caenepeel and Goyvaerts [“Monoidal Hom-Hopf algebras,” Commun. Algebra 39, 2216–2240 (2011)] and let G be a crossed product group \documentclass[12pt]{minimal}\begin{document}${\sl Aut}_{mHH}(H)\times {\sl Aut}_{mHH}(H)$\end{document}AutmHH(H)×AutmHH(H). The main aim of this paper is to provide new examples of braid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…In what follows, we will recall from [1,4,5,7] the definitions of monoidal Hom-associative algebras, monoidal Hom-coassociative coalgebras, monoidal Hom-modules and monoidal Hom-comodules. The reader could also refer to [14,16,17].…”
Section: Preliminariesmentioning
confidence: 99%
“…In what follows, we will recall from [1,4,5,7] the definitions of monoidal Hom-associative algebras, monoidal Hom-coassociative coalgebras, monoidal Hom-modules and monoidal Hom-comodules. The reader could also refer to [14,16,17].…”
Section: Preliminariesmentioning
confidence: 99%
“…For this, Panaite and Staic [10] gave some interesting constructions in the case of Hopf algebra. Motivated by this, Yang [19], [20], Liu [4] and You [21] generalized their work to multiplier Hopf algebra, weak Hopf algebra and monoidal Hom-Hopf algebra cases, also the authors obtain some new classes of braided crossed categories which provided some solutions to the quantum Yang-Baxter equation over π.…”
Section: Introductionmentioning
confidence: 95%
“…In [29,31] Yau proposed the definition of quasitriangular Hom-Hopf algebras and showed that each quasitriangular Hom-Hopf algebra yields a solution of the Hom-Yang-Baxter equation. Meanwhile, several classes of solutions of the Hom-Yang-Baxter equation were constructed from different respects, including those associated to Hom-Lie algebras [5,25,29,30], Drinfeld (co)doubles [2,34,35] and Hom-Yetter-Drinfeld modules [3,10,13,14,18,26,33].…”
Section: Introductionmentioning
confidence: 99%